Bis(6‐diphenylphosphino‐acenaphth‐5‐yl)sulfoxide: A New Ligand for Late Transition Metal Complexes. Issue 40 (2nd September 2020) - Meyer, Fabio; Hupf, Emanuel; Lork, Enno; Grabowsky, Simon; Mebs, Stefan; Beckmann, Jens
Abstract : The synthesis of the new ligand bis(6‐diphenylphosphinoacenaphth‐5‐yl)sulfoxide, [6‐(Ph2 P)‐5‐Ace‐6]2 ‐SO (1 ), is presented along with six transition metal complexes thereof, namely, 1· MCl (M = Rh, Cu, Ag, Au) and 1· MCl2 (M = Ni, Pd). Within these novel complexes, close metal‐sulfur distances are observed and the nature of the M–S coordination, as well as the response of the + S–O – bond, are investigated in detail with a set of spectroscopic, crystallographic and real‐space bonding indicators. Abstract : The new ligand bis(6‐diphenylphosphinoacenaphth‐5‐yl)sulfoxide, [6‐(Ph2 P)‐5‐Ace‐6]2 ‐SO, forms a variety of transition metals complexes with sulfur‐metal interactions.